Discourse of Yemeni TV broadcasters and the dilemma of regime criticism, 2015–19. (1st April 2020) - Almahfali, Mohammed
The discourse of the Yemeni TV broadcasters has undergone major changes since the Arab Spring in 2011. Moreover, since the outbreak of Civil War in 2015, this discourse has been diverse and has become a clear reflection of the contexts in which it is produced. This article analyses Yemeni media discourse by analysing the titles of news reports published on YouTube by five Yemeni TV channels belonging to five diversified discourses in terms of political, ideological, cultural and social orientation. The article adopts discourse framing as a methodological tool, with which we can address media discourse and thus reveal its social, political and cultural contexts. The article concludes that Yemeni TV broadcasters' discourse depends on a limited number of keywords that have a cognitive and cultural balance in Yemeni society, words originally taken from cultural, religious and social backgrounds in the collective memory of Yemen. Knowing these keywords can be employed in different dimensions. While it can contribute to developing the recipient awareness, it can also help to raise the degree of professionalism in media performance in Yemen, especially in the stage of peace-building and post-war.